Bone mineral density differences across female olympic lifters, power lifters, and soccer players - Jeon, W.; Harrison, J. M.; Stanforth, P. R.; Griffin, L. (The Journal of Strength and Conditioning Research, 2021)
Athletic training improves bone mineral density (BMD) through repeated mechanical loading. The location, intensity, and direction of applied mechanical pressure play an important role in determining BMD, making some sports more advantageous at improving BMD at specific regions. Thirty-seven (10 power lifters [PL], 8 Olympic lifters [OL], 8 soccer players [SP], and 11 recreationally active [RA]) women participated in a cross-sectional study. We measured lumbar spine (L1-L4), femoral neck, total-body BMD, and overall body composition (total fat mass, lean mass, percent body fat) with dual-energy x-ray absorptiometry. All athletic groups had greater total BMD than RA (p = 0.01 [PL]; p < 0.001 [OL]; p = 0.01 [SP]). Olympic lifters had the highest total BMD than all other athletic groups. Olympic lifters had the significantly greater total BMD than PL (p = 0.018), but there was no difference in total BMD between PL and SP. As compared with RA, OL showed greater BMD at both the total lumbar spine (p = 0.002) and the femoral neck (p = 0.007), whereas PL showed greater BMD only for the total lumbar spine (p = 0.019) and SP showed greater BMD only for the femoral neck (p = 0.002). Olympic-style lifting includes both high-impact and odd-impact loading modalities that are associated with the highest BMD at both the lumbar spine and femoral neck.